Unlocking the Medinan Qur’an - Sinai, Nicolai 1976- (Brill, 2022)
"The Qur'anic surahs and passages that are customarily taken to postdate Muhammad's emigration to Medina occupy a key position in the formative period of Islam: they fundamentally shaped later convictions about Muhammad's paradigmatic authority and universal missionary remit; they constitute an important basis for Islam's development into a religion with a strong legal focus; and they demarcate the Qur'anic community from Judaism and Christianity. The volume exemplifies a rich array of approaches to the challenges posed by this part of the Qur'an, including its distinctive literary and doctrinal features, its relationship to other late antique traditions, and the question of oral composition"--
Keywords: Medinische Suren; Koran; Geschichte; Islam; Qurʼan / History of Qurʼanic events; Qurʼan / Criticism, Textual; Qurʼan / Criticism, interpretation, etc; Qurʼan / History; Aufsatzsammlung